Pembangunan Ekonomi Lokal dalam Perspektif Pembangunan Partisipatif: Analisis Sosiologis Aktivitas Pedagang di Pasar Aur Kuning - Dwi Pramana Putra; Cherli Aftariani; Alvit Alvit; Akdila Bulanov (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the role of traditional markets as socio-economic spaces in local economic development, focusing on traders’ activities at Pasar Aur Kuning. Drawing on the historical role of markets in shaping Minangkabau nagari life and the urban evolution of Bukittinggi from Pakan Kurai to contemporary market governance, this paper positions Pasar Aur Kuning as a vital continuation of market traditions that sustain the city’s economy. Using a library research approach and sociological analysis of written sources, the study interprets how traders’ practices reflect community participation in local economic development (LED). The discussion shows that open access to trading spaces, distribution patterns from wholesale to retail, job creation, and multiplier effects on surrounding support sectors constitute concrete forms of community participation. Infrastructure support such as road accessibility and the nearby bus terminal strengthens the market’s function as a node for the mobility of goods, people, and social interaction. Sociologically, the market operates not only as a site of economic exchange but also as an arena where social networks, solidarity, and intergroup relations are continuously formed. These findings affirm that traders’ activities at Pasar Aur Kuning represent social practices that directly contribute to a dynamic, inclusive, and sustainable local economy.